Textilní výroba v českých zemích ve 13.-15. století : poznání textilní produkce na základě archeologických nálezů - Březinová, Helena (2007)
Engl. Zsfassung u.d.T.: Textile manufacture in the Czech lands in the 13th-15th centuries. Underständing textile production on the basis of archaeological finds